Sexual Behavior and Sexually Transmitted Infection Outcomes Among Men Who Have Sex With Men and Transgender Women Participating in a Study of the Timing of Antiretroviral Therapy in Lima, Peru. Issue 12 (December 2020) - Montaño, Michalina A.; Alfaro, Ricardo; Ness, Tara; Ganoza, Carmela; Gonzales, Pedro; Sanchez, Jorge; Lama, Javier R.; Duerr, Ann C.
Abstract : Background: We assessed sexual behavior and incidence of sexually transmitted infections (STIs) among men who have sex with men and transgender women participating in Sabes, a study of an expanded treatment as prevention strategy focused on early diagnosis and treatment of HIV infection in Lima, Peru (2013–2017). Methods: Sabes participants were tested monthly for HIV to identify acute or early infections, and HIV-positive participants were randomized to receive antiretroviral therapy immediately (immediate arm) or after 24 weeks (deferred arm) during a 48-week follow-up period. Sexual behavior was assessed at randomization (baseline) and every 12 weeks thereafter. Participants were tested for urethral and rectal chlamydia and gonorrhea and for syphilis at baseline, 12, 24, and 48 weeks. We describe patterns of sexual behavior during the 48-week follow-up period and compare sexual behavior and STI incidence between study arms. Results: After randomization, 207 HIV-positive participants completed questionnaires and STI testing at 2 or more visits. After HIV diagnosis, participants in both arms reported increases in condom use with main and casual partners and decreased drug and alcohol use before or during anal sex. We observed no between-arm differences in sexual behavior. Deferred arm participants had higher incidence of chlamydia (incidence rate ratio, 2.33; 95% confidence interval, 1.14–4.77) but not gonorrhea or syphilis. Conclusions: Despite reported increases in condom use, the overall high incidence of STIs reflects some ongoing condomless sex among HIV-positive men who have sex with men and transgender women, highlighting the importance of regular STI screening and counseling to support consistent condom use among HIV-positive individuals at risk for STIs. Abstract : A randomized study of timing of antiretroviral therapy initiation (immediate vs. deferred) among Peruvian men who have sex with men and transgender women found no between-arm differences in sexual behavior and high sexually transmitted infection incidence overall.Supplemental digital content is available in the text.